2017
DOI: 10.1371/journal.pone.0182356
|View full text |Cite
|
Sign up to set email alerts
|

BARD1 serum autoantibodies for the detection of lung cancer

Abstract: PurposeCurrently the screening for lung cancer for risk groups is based on Computed Tomography (CT) or low dose CT (LDCT); however, the lung cancer death rate has not decreased significantly with people undergoing LDCT. We aimed to develop a simple reliable blood test for early detection of all types of lung cancer based on the immunogenicity of aberrant forms of BARD1 that are specifically upregulated in lung cancer.MethodsELISA assays were performed with a panel of BARD1 epitopes to detect serum levels of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The over-expression of BARD1 isoforms is strongly correlated with tumor progression, specifically in non-small-cell lung cancer (NSCLC) [ 20 , 51 , 78 ]. Based on these evidences Irminger-Finger et al have developed a blood test for the early detection and diagnosis of lung cancer based on capturing autoimmune antibodies against BARD1 antigens [ 91 ]. Additional studies are needed to verify the efficacy of this test in detection of lung cancer and it will be very interesting to extend this experimentation to other cancers such as neuroblastoma, ovarian and breast cancer.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…The over-expression of BARD1 isoforms is strongly correlated with tumor progression, specifically in non-small-cell lung cancer (NSCLC) [ 20 , 51 , 78 ]. Based on these evidences Irminger-Finger et al have developed a blood test for the early detection and diagnosis of lung cancer based on capturing autoimmune antibodies against BARD1 antigens [ 91 ]. Additional studies are needed to verify the efficacy of this test in detection of lung cancer and it will be very interesting to extend this experimentation to other cancers such as neuroblastoma, ovarian and breast cancer.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Certainly, lung cancer is five times more common in smokers with COPD than in those with normal lung function 61,62 and COPD is an independent risk factor for lung carcinoma, mostly for squamous cell carcinoma 63 . Despite the advances in early identification and in the therapeutic management of both COPD and lung cancer the underlying networking mechanisms are far from being well established resulting in poor prognosis [64][65][66][67][68][69] . Many epidemiological studies have showed that emphysema and air flow obstruction are both involved as risk factors for lung cancer incidence and death, but their relative roles have not been fully clarified.…”
Section: Copd and Lung Cancermentioning
confidence: 99%
“…The above phenomenon may correlate with the fact that BARD1 functions as a factor of apoptosis, unrelated to BRCA1. Isoforms excessively expressed in tumor cells do not have suppressor functions, which leads to faster progression and poor prognosis [43,44,4]. [48].…”
Section: Utility Of Bard1 In Surveillance Programsmentioning
confidence: 99%